Decreased tryptophan and increased kynurenine levels in mastocytosis associated with digestive symptoms. Issue 3 (24th December 2015) - Georgin‐Lavialle, S.; Launay, J.‐M.; Côté, F.; Soucié, E.; Soria, A.; Damaj, G.; Moura, D. S.; Canioni, D.; Hanssens, K.; Chandesris, M.‐O.; Barète, S.; Dubreuil, P.; et al.
Abstract: The main metabolism pathway of tryptophan is protein formation, but it can also be metabolized into serotonin and kynurenine. Indoleamine 2, 3‐dioxygenase (IDO) is the enzyme that catalyzes the degradation of tryptophan into kynurenine. Mastocytosis is a heterogeneous disease characterized by mast cell accumulation in various tissues with 57% of patients having gastrointestinal involvement. We studied tryptophan metabolism in mastocytosis patients displaying or not gastrointestinal features and healthy subjects ( n = 26 in each group). Mastocytosis patients with digestive symptoms displayed significantly increased kynurenine level and IDO activity as compared to healthy controls and mastocytosis patients without digestive symptoms. This could be linked to mast cell‐mediated digestive inflammation among patients with mastocytosis. This work is the first focusing on kynurenine pathway in a mast cell disease and could help to understand the pathogenesis of digestive features in mastocytosis as well as in other mast cell‐mediated diseases.